Between Sacred Texts and Local Traditions: The Dialectics of Worship and Culture in Aceh - Husnaini, Husnaini; Ismail, Sherif Mohamed A.; Syihab, Mahdi Abdullah; Jafar, Muhammad; Zulhamdi, Zulhamdi; Keumala Ulfah, Almira (Religió Jurnal Studi Agama-agama, 2025)
The encounter between religion and various cultures often results in a dynamic interaction, as it has to adapt to the existing traditions lived by the people. Examining such studies will reveal the tension and the dialectical dimension, helping us better understand how people perceive religion. This article aims to understand the relationship between Islamic rituals and Acehnese cultural practices, an area known as the “Veranda of Mecca”. By analyzing and interpreting extensive sources from a literature review, including academic literature, local religious texts, and historical archives, this qualitative research reveals that religious practices in Aceh, particularly the Commemoration of the Prophet Muhammad’s birth, congregational dhikr, tahlilan, and tarekat traditions, are the result of a centuries-long dialectic between Islamic teachings and the local traditions. Furthermore, it reveals two main views toward the religion: the textual view, which emphasizes the essence of the teachings and rejects cultural innovation, and the contextual view, which accepts acculturation. These approaches sometimes trigger tension, but also enrich the treasury of Islam and strengthen the social solidarity of the Acehnese people. This study underscores the importance of an inclusive, dialogical understanding as an interpretive resource for building a distinctive, harmonious religious identity in Aceh.